Genetic polymorphism in bubaline mLYS (Exon-IV) and its effect on serum lysozyme activity and somatic cell count - NIHAR RANJAN SAHOO; PUSHPENDRA KUMAR; T K BHATTACHARYA; B BHUSHAN; A K TIWARI; A SHARMA (Indian Journal of Animal Sciences, 2016)
Animals (280) consisting of 4 different buffalo breeds (Murrah, Mehsana, Surti and Bhadawari) spread over 6 different farms across the country were used for this study. A 230 bp fragment spanning from intron-III to exon-IV was screened for SSCP which revealed frequent occurrence of AB genotype and A allele. Although, different values of lysozyme activity and somatic cell count were observed in Murrah buffalo across the genotypes and seasons, no statistically significant association was observed. Nucleotide analysis revealed A allele differed from B and C allele by 2 and 3 nucleotide substitutions, respectively, out of which one was present in intronic region in both cases. The polymorphism identification and characterization may provide a baseline tool for future studies to further delineate the role of this gene as a putative candidate gene for selection against mastitis.